Weed diversity and microbial responses to glyphosate dissipation in amended coffee soils - AI YANTI RISMAYANTI; YAYAN SUMEKAR; DEDI WIDAYAT; YUYUN YUWARIAH; ADITYA MURTILAKSONO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rismayanti AY, Sumekar Y, Widayat D, Yuwariah Y, Murtilaksono A. 2026. Weed diversity and microbial responses to glyphosate dissipation in amended coffee soils. Biodiversitas 27 (1): d270144. https://doi.org/10.13057/biodiv/d270144. Glyphosate dissipation in tropical coffee soils is an important ecological concern because residue dynamics may influence weed communities and soil microbial activity. Understanding how soil amendments modify these responses is essential for strengthening sustainable weed management in perennial crops. This study evaluated the effects of biochar and manure on glyphosate dissipation, weed dynamics, and microbial respiration in Arabica coffee soils. A split-plot field experiment with three replications was conducted, combining two organic amendments and six glyphosate doses; weed biomass was analyzed using ANOVA, while glyphosate residues and soil microbial respiration were evaluated descriptively using composite samples. Before herbicide application, 19 weed species were recorded, dominated by Panicum repens, Cynodon dactylon, and Amaranthus spinosus. Following glyphosate application, weed diversity temporarily declined from H′ = 2.27 to 2.12 at 14 days after application (DAA) and subsequently recovered to 2.29-2.33 by 28-42 DAA, while community similarity remained high (>97%). Weed biomass was significantly affected by glyphosate dose at all observation times, with a significant interaction between glyphosate dose and soil amendment detected only at 28 DAA. Organic amendments, particularly biochar and manure, were associated with lower weed biomass and a less pronounced decline in weed diversity during the early phase of glyphosate application. Amended soils showed higher measured microbial respiration compared with unamended soils during the observation period. Glyphosate residue concentrations showed a faster apparent decline in amended soils, with lower measured values observed by 42 days after application. These findings indicate that organic materials are associated with differences in glyphosate dissipation and soil microbial respiration patterns. However, glyphosate residue and microbial respiration data were derived from non-replicated composite samples; therefore, observed trends should be interpreted cautiously. The use of organic amendments, particularly biochar, was associated with changes in weed biomass, microbial respiration patterns, and glyphosate dissipation in coffee soils, indicating their potential relevance for integrated and environmentally conscious weed management.